2018
DOI: 10.1186/s12867-018-0114-7
|View full text |Cite
|
Sign up to set email alerts
|

The Dictyostelium discoideum homologue of Twinkle, Twm1, is a mitochondrial DNA helicase, an active primase and promotes mitochondrial DNA replication

Abstract: BackgroundDNA replication requires contributions from various proteins, such as DNA helicases; in mitochondria Twinkle is important for maintaining and replicating mitochondrial DNA. Twinkle helicases are predicted to also possess primase activity, as has been shown in plants; however this activity appears to have been lost in metazoans. Given this, the study of Twinkle in other organisms is required to better understand the evolution of this family and the roles it performs within mitochondria.ResultsHere we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…The NTDs are always on the 5′ side of the DNA relative to the helicase domains to assist primer synthesis ( Supplementary Figure S5 ). Like gp4, Twinkle helicases from plants and lower eukaryotes can catalyze primer synthesis ( 62 , 63 ). However, the primase active site residues are mutated in vertebrate Twinkle ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NTDs are always on the 5′ side of the DNA relative to the helicase domains to assist primer synthesis ( Supplementary Figure S5 ). Like gp4, Twinkle helicases from plants and lower eukaryotes can catalyze primer synthesis ( 62 , 63 ). However, the primase active site residues are mutated in vertebrate Twinkle ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NTDs are always on the 5’-side of the DNA relative to the helicase domains to assist primer synthesis (Supplementary Figure 5). Like gp4, Twinkle helicases from plants and lower eukaryotes can catalyze primer synthesis (60,61). However, the primase active site residues are mutated in vertebrate Twinkle (11).…”
Section: Discussionmentioning
confidence: 99%
“…Twinkle primase domain is composed of ZBD and RPD; the ZBD interacts with the DNA template during primer synthesis and the RPD forms RNA polymerases (Kato et al, 2003). However, the primase domain of metazoan Twinkle lacks the critical residues for primase function and does not have primase activity in vitro (Harman and Barth, 2018). It was reported that several recessive mutations in Twinkle primase domain can lead to MDS in human (Hakonen et al, 2007;Hartley et al, 2012;Vi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%